1967
DOI: 10.1063/1.1754804
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Tunable, Narrow-Band Organic Dye Lasers

Abstract: Efficient spectral narrowing, and tunability over a wide spectral range, has been demonstrated in solid and liquid organic dye lasers using diffraction gratings as cavity reflectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
119
0
3

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(122 citation statements)
references
References 6 publications
0
119
0
3
Order By: Relevance
“…At that time, the most popular excitation sources were nitrogen (12) or frequency-doubled ruby lasers, used with or without a pulsed dye laser (13). Both devices had serious limitations with short-lived fluorophores.…”
Section: Exploring a New Fieldmentioning
confidence: 99%
“…At that time, the most popular excitation sources were nitrogen (12) or frequency-doubled ruby lasers, used with or without a pulsed dye laser (13). Both devices had serious limitations with short-lived fluorophores.…”
Section: Exploring a New Fieldmentioning
confidence: 99%
“…The first attempts to develop solid-state dye lasers were reported in the late 1960s [1,2]. Ever since, there have been intensive efforts to achieve the incorporation of organic dyes in solid matrices that might replace conventional liquid dye lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the applications deal with the germicidal effects of UV for disinfecting a wide variety of organisms. This use has been suggested for airborne infections in hospitals, schools, and other places where large groups of people may congregate, such as human shelters during natural catastrophes (26,27); water purification for hunidifiers in hospitals (28); providing potable water supplies on transoceanic ships (29); and so forth. Intense sources of ultraviolet are used in photobiological research (30) and the use of ultraviolet in holography has been suggested (31).…”
Section: Uses Of Ultraviolei Radiationmentioning
confidence: 99%